Coping styles of new undergraduate mathematicians - ELLIE DARLINGTON (Metaichmio Publications, 2017)
The academic transition between school and university mathematics is challenging for many students, due to the nature of mathematics. This paper reports on the results of a study in which the Coping Styles Questionnaire (CSQ) was distributed to 186 first-year mathematicians. Barely-remarkable gender differences were found in students' responses, which might suggest that gender stereotypes in mathematics may not be as extreme as many believe. Furthermore, findings suggest that questionnaires such as the CSQ could be used to identify students' coping styles and consequently help them adopt effective coping strategies for the secondary-tertiary mathematics transition.